Sistem Informasi Bantuan Keuangan untuk Pengelolaan dan Distribusi Dana - Amirullah (Jurnal Sistem Komputer (SISKOM), 2021)
The Financial Assistance Information System is designed to streamline the process of managing and distributing financial aid. This system offers a user-friendly interface for applicants to submit their requests, check the status of their applications, and receive updates. Additionally, it enables administrators to efficiently review applications, verify eligibility, and allocate funds. By incorporating features such as automated eligibility checks, real-time status updates, and comprehensive applicant records, the system enhances transparency and operational efficiency. The system also includes robust reporting and analytics tools that assist management in making data-driven decisions. Furthermore, it supports integration with various payment platforms, ensuring secure and timely disbursement of funds. Overall, the Financial Assistance Information System aims to improve the management of financial aid programs, ensuring that assistance reaches those in need promptly and effectively, thereby enhancing both applicant experience and administrative processes.